Penguatan Ekonomi Syariah Berbasis Tafsir Ayat Muamalah Bagi Pelaku Umkm Desa Tangkit - Zulaika Zulaika; Muhammad Arifin; Siti Risyda Mahmuda; Putri Mayang Sari; Revi Rahmadani; Thecy Junelmi; Fajrul Falah (Civiliza Publishing, 2025)
This study addresses the need to strengthen grassroots Islamic economic practices among rural UMKM by integrating Qur’anic guidance on muʿāmalah into daily business activities. It aims to examine how the interpretation of muʿāmalah verses can serve as a foundation for enhancing sharia-based economic behavior among UMKM in Tangkit Village. A participatory, practice-oriented approach was implemented through interactive lectures, focused group discussions, question-and-answer sessions, and simulations of sharia-compliant transactions, covering muʿāmalah interpretation, the principle of lā ḍarar wa lā ḍirār, halal financial management, and fair and transparent marketing. The findings reveal improved understanding of Islamic economic principles, more orderly and ethical transaction practices, and increased competitiveness of local products, especially processed pineapple. However, challenges remain in the form of limited capital, low technological adoption, and varying levels of religious and Islamic economic literacy. Overall, tafsir-based empowerment proves effective but requires continuous mentoring, practice-based capacity building, and sustained reinforcement of muʿāmalah literacy to ensure consistent and long-term implementation of sharia principles while supporting inclusive and equitable local economic development.